Perancangan Interior Lobby & Area Pameran Museum Antariksa Surabaya - Hendy Darma Saputra (Intra, 2017)
Man is a curious creature, every age is increasingly thirsty to explore what nature has. Of all the discoveries of humanity that ever existed the most interesting and great mystery is space and space, this invention was initiated by the father of modern astronomy Galileo Galilei (1564-1642).At first humans recognize the astrology system and use it as a navigation tool / direction but now humans have understood the space is much better and utilize the knowledge that can be to create everyday technology that can improve the quality of human life. The science of outer space is no less important than any other science because we live in an age where humans have realized that there is more beyond our planet earth but, in Surabaya and also the general knowledge of society in Surabaya about space is very less because of lack of Facilities that can satisfy the public's curiosity.